Soil-water characteristic curve and consolidation behavior of a compacted silt - Trinh, Minh Thu (2011)
Measurement of the soil-water characteristic curve (SWCC) in the laboratory is commonly conducted under zero confining pressure. However, in the field, the soil is under a confining stress. Therefore, it is important to study the effects of the confining stress on SWCC. In addition, the consolidation curve is normally generated under saturated conditions. However, the soil above the water table is usually unsaturated. Hence, it is also necessary to investigate the effects of matric suction on the characteristics of the consolidation curves. This paper presents the SWCCs under different net confining stresses and the isotropic consolidation curves under different matric suctions that describe the volume change characteristics of unsaturated soils with respect to stress state variables, net normal stress, and matric suction. A series of SWCCs was determined for statically compacted silt specimens in a triaxial cell apparatus under different net confining stresses. Isotropic consolidation tests under different matric suctions were also carried out. The results of the SWCC tests show that the air-entry value increased with increasing net confining stress. The yield points (i.e., yield suction, s0) obtained from the SWCC tests also increased with increasing net confining stress. The results of isotropic consolidation tests indicate the strong influence of matric suction on compressibility and stiffness of the compacted silt specimens.